A Test of the Hypothesis That D(2)O Affects Circadian Oscillations by Diminishing the Apparent Temperature - Caldarola, Patricia C. (1974)
The period (τ) of a circadian pacemaker in the cockroach Leucophaea maderae is a nonmonotonic function of temperature. The slope of the curve (τ as a function of temperature) is negative at 20° and positive at 30°. When these insects are deuterated at 20° and 30° the period (τ) of the pacemaker lengthens in both cases, although there is a marked temperature dependence of D(2)O action. The increase in τ is nearly three times greater at 20° than 30°. This observation is a flat contradiction of a prediction made earlier that when D(2)O affects circadian pacemakers it does so by diminishing the apparent temperature of the cell. That prediction, however, involves an assumption that may well be unfounded. Unless D(2)O acts nonselectively on all the components in the system regulating τ, the prediction we sought to test is unfounded; and if D(2)O does not act nonselectively, the observed temperature dependence of D(2)O action is understandable in terms of simulating a lower temperature for those components it does affect.